1988
DOI: 10.1126/science.2452480
|View full text |Cite
|
Sign up to set email alerts
|

Dextran Sulfate Suppression of Viruses in the HIV Family: Inhibition of Virion Binding to CD4 + Cells

Abstract: The first step in the infection of human T lymphocytes by human immunodeficiency virus type 1 (HIV-1) is attachment to the target cell receptor, the CD4 antigen. This step may be vulnerable to attack by antibodies, chemicals, or small peptides. Dextran sulfate (molecular weight approximately 8000), which has been given to patients as an anticoagulant or antilipemic agent for more than two decades, was found to block the binding of virions to various target T lymphocytes, inhibit syncytia formation, and exert a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
222
1
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(228 citation statements)
references
References 16 publications
4
222
1
1
Order By: Relevance
“…We have found that pentosan polysulphate, suramin, aurintricarboxylic acid and Evans Blue, in addition to their inhibitory effects on virus replication (Baba et al, 1988 a, b, c;Balzarini et al, 1986) and virus adsorption to the cell membrane (Mitsuya et al, 1988;Baba et al, 1988a, b;Schols et al, 1988), are also capable of inhibiting giant cell formation. The IC5o values obtained with this flow cytometric method for monitoring giant cell formation corresponded closely to the ICs0 values recorded on the basis of microscopic enumeration of giant cells (M. Baba et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…We have found that pentosan polysulphate, suramin, aurintricarboxylic acid and Evans Blue, in addition to their inhibitory effects on virus replication (Baba et al, 1988 a, b, c;Balzarini et al, 1986) and virus adsorption to the cell membrane (Mitsuya et al, 1988;Baba et al, 1988a, b;Schols et al, 1988), are also capable of inhibiting giant cell formation. The IC5o values obtained with this flow cytometric method for monitoring giant cell formation corresponded closely to the ICs0 values recorded on the basis of microscopic enumeration of giant cells (M. Baba et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Since the primary interaction appears to be dependent on charge density rather than a particular structural motif (57), it seems unlikely that the specificity essential for effective therapeutic treatment is present. This does not bode well for drug development based on polyanions such as sulfated polysaccharides (2,24,35), carboxylated albumins (26,51), porphyrins (13,49), or DNA or RNA derivatives (31). Nevertheless, the unusual basicity observed for the CXCR4-using viruses may, in this particular case, permit anion-based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[66,68] In 1988, two independent reports published within months of each other, reported that polyanions such as 1 and 2 reduced the HIV absorption (referred later to as 'entry') on to CD4þ host cells. [69,70] In addition, the study showed that dextran sulfate chain length has no effect on efficacy, however the chain lengths of 2 had a profound effect on HIV-1 inhibition where unfragmented heparin (M w % 15 000 g Á mol À1 ) and long chain fragmented heparin (M w % 11 000 g Á mol À1 ) had the highest efficacy. [70] Although the principle reason for HIV inhibition by sulfated polysaccharides was known, the exact mechanism and the binding site of these polyanionic inhibitors was not known.…”
Section: Polysaccharide Entry Inhibitorsmentioning
confidence: 99%
“…[66,69,70] Due to these high in vitro potencies, clinical trials were rapidly set up in the late 1980s to study the efficacy upon systemic administration in HIV-1 infected patients. [129,130] Dextran sulfate (1) was selected as the drug of choice due to low anticoagulant activity compared to heparin (2) and because previous clinical experience in administration of the drug provided a better understanding of the pharmacokinetics and toxicity.…”
Section: Applications and Perspectives Of Anti-hiv Polymer Therapeuticsmentioning
confidence: 99%